(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
In this paper, we introduce and investigate the notion of contra π gγ-continuous functions by utilizing π gγ-closed sets [31]. We obtain fundamental properties of contra π gγ-continuous functions and discuss the relationships between contra π gγ-continuity and other related functions.